2021
DOI: 10.1111/ijac.13734
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial response of ZnO‐MgO nanocomposites at various compositions

Abstract: ZnO‐MgO nanocomposites were prepared by a co‐precipitation method and afterward compared with pristine ZnO and MgO accordingly. XRD and EDX spectra were used to confirm the crystal structure and crystallite size of these materials. X‐ray diffraction analysis shows that antibacterial activity of ZnO:MgO composite enhances with crystallite size reduction ~1.34 times in comparison to pristine ZnO or MgO specimens, accompanied by domination of defect generation over defect annihilation activity. Besides, average p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
(59 reference statements)
1
1
0
Order By: Relevance
“…e findings demonstrated that the structure resembled cubic shape in nature. ese results agreed with reported works [26,27]. Debye-Scherrer's formula was used to compute the crystalline size of zinc oxide, as shown in Table 1:…”
Section: X-ray Diffractionsupporting
confidence: 88%
“…e findings demonstrated that the structure resembled cubic shape in nature. ese results agreed with reported works [26,27]. Debye-Scherrer's formula was used to compute the crystalline size of zinc oxide, as shown in Table 1:…”
Section: X-ray Diffractionsupporting
confidence: 88%
“…For instance, the ZnO-MgO and CuO-MgO-ZnO nanocomposites prepared by a co-precipitation method showed better antibacterial activity than pure MgO nanoparticles. [16,17] Even though substantial works reported that the antibacterial ability, which is closely associated with oxygen vacancies concentration, can be improved by using the methods of metal doping, non-metal doping, co-doping and co-precipitation. However, the uneven dispersion of doping ions and inorganic composites in MgO nanoparticles might result in the unstable antibacterial effect.…”
Section: Introductionmentioning
confidence: 99%